2019
DOI: 10.3390/ijerph16183376
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Sales in Primary Care in Hubei Province, China: An Analysis of 2012–2017 Procurement Records

Abstract: The over-use of antibiotics has been identified as a major global challenge, where there is insufficient knowledge about the use of antibiotics in primary healthcare settings, especially at a population level. This study aims to investigate the trends and patterns of antibiotic sales in primary care in Hubei, China over a six-year period from 2012 to 2017. Antibiotic sales were expressed with Defined Daily Doses per 1000 inhabitants per day (DIDs) and compared with European countries using the 12 quality indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…These changes coincided with the multiple interventions that regulate the use of antibiotics in China, including the 2012 Administrative Rules for the Clinical Use of Antibiotics issued by the Ministry of Health. This administration intervention appeared to work better according to the findings of this study and others (Zhang et al, 2019). In addition to persuasive guidelines, penalties for violating these administrative rules and measures, such as downgraded accreditation and service fee levels and dismissal of managers, were applied.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These changes coincided with the multiple interventions that regulate the use of antibiotics in China, including the 2012 Administrative Rules for the Clinical Use of Antibiotics issued by the Ministry of Health. This administration intervention appeared to work better according to the findings of this study and others (Zhang et al, 2019). In addition to persuasive guidelines, penalties for violating these administrative rules and measures, such as downgraded accreditation and service fee levels and dismissal of managers, were applied.…”
Section: Discussionmentioning
confidence: 84%
“…Antimicrobial resistance (AMR) driven by antibiotic consumption is a growing threat to global public health (Song, 2018;Zhang et al, 2019). China is among the world's largest producers and consumers of antibiotics, which are widely used for disease treatment in humans and livestock, as well as prophylaxis and growth promoters for the latter (Qiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high prevalence of parenteral administration of antibiotics has attracted increasing safety concerns in China. Studies showed that 36% to 60% of antibiotics were administered through parenteral injections in primary care settings in China [29][30][31].…”
Section: Antibiotic Prescribing Patternsmentioning
confidence: 99%
“…The domination of broad-spectrum antibiotics in antibiotic prescribing in Hubei of China is comparable to ndings of other studies. A study monitoring antibiotic sales in primary cares in Hubei showed that broad-spectrum antibiotics were increasingly used in recent years, rising from 74.87% as a proportion of antibiotic sales in 2012 to 85.69% in 2017 [31]. This is not unique to China.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…In addition, the high prevalence of parenteral administration of antibiotics has attracted increasing safety concerns in China. Studies showed that 36-60% of antibiotics were administered through parenteral injections in primary care settings in China [29][30][31].…”
Section: Data Collectionmentioning
confidence: 99%